Iceland's natural experiment in education reform - Tinna Laufey Ásgeirsdóttir; Gísli Gylfason; Gylfi Zoega (University of Iceland, Institute of Economic Studies (IoES), 2022)
We use a change in Iceland's education system as a natural experiment to measure the effect of years spent in upper secondary school on subsequent first year outcomes at university. The duration of Icelands upper-secondary education was shortened by one year through compression of the curriculum. The study benefits from a large variation in the age within both the treatment and the control groups, allowing us to separate the effects of shorter upper-secondary education from the effect of age when university studies are initiated. We find that shorter upper-secondary education, three years instead of the previous four, leads to first-year university students completing fewer credits, getting a lower average grade in completed courses, and being more likely to drop out. Results indicate that the effects are partly explained by the age at university enrollment. This applies particularly to women while men are adversely affected even when age is accounted for.
Keywords: I21; I26; 330; Years of schooling; upper-secondary school; university grades